2012
DOI: 10.1007/s11250-012-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inclusion of fermented cottonseed meal on growth, cecal microbial population, small intestinal morphology, and digestive enzyme activity of broilers

Abstract: Two experiments were conducted to test the feeding value of fermented cottonseed meal (FCSM) in broilers. In experiment 1, 480 1-day-old male yellow-feathered broilers were allocated into 4 dietary treatments with 6 replicates (20 birds per replicate) to examine the effects of FCSM on the growth response of chickens. Experimental feeding was performed for 6 weeks in two phases (starter, days 0 to 21; finisher, days 22 to 42). FCSM was used at 0, 40, 80, and 120 g/kg levels to replace soybean meal in the basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 19 publications
5
63
1
1
Order By: Relevance
“…Chiang et al (2010) demonstrated that broilers fed fermented rapeseed meal had greater Lactobacilli counts in ceca digesta. In the present study, the broilers fed FCSM-1 diets significantly increased the number of total anaerobic bacteria in ceca digesta compared with CSM diet on day 42, which is consistent with the result of Sun et al (2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Chiang et al (2010) demonstrated that broilers fed fermented rapeseed meal had greater Lactobacilli counts in ceca digesta. In the present study, the broilers fed FCSM-1 diets significantly increased the number of total anaerobic bacteria in ceca digesta compared with CSM diet on day 42, which is consistent with the result of Sun et al (2013b).…”
Section: Discussionsupporting
confidence: 90%
“…38 Similarly, it has been reported that dietary inclusion of prebiotics (e.g., fructooligosaccharide and mannanoligosaccharide) or fermented feed (e.g., fermented cottonseed, soybean, and rapeseed meal) also result in increased villus height and villus height:crypt depth ratio in the small intestine of chicken. [39][40][41][42][43] Such morphology alterations are not likely a direct effect of these dietary supplements, but an indirect effect through the manipulation of gut microbiome structure. 40 Intestinal morphology change can also be an outcome of infections caused by enteric pathogens.…”
Section: Microbiome Affects Intestinal Morphology and Physiologymentioning
confidence: 99%
“…For instance, the activities of amylase and protease are elevated in broilers fed diets containing fermented cottonseed meal or fructooligosaccharides. 40,43 Feeding broilers with fermented soybean meal instead of unfermented soybean meal increased the activities of protease, trypsin and lipase. 41 It was concluded that these diets stimulate certain bacteria (e.g., Bifidobacterium and Lactobacillus) that can increase digestive enzyme activity, while suppressing some bacteria (e.g., Escherichia coli) that can either impair digestive enzyme secretion by damaging the villus and microvillus of mucosa or secrete proteolytic enzyme to degrade digestive enzymes.…”
Section: Microbiome Affects Intestinal Morphology and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages are that ferrous sulfate can cause feed turning black, whereas NaOH often destroys the taste of CSM. Biodetoxification techniques usually utilize some fungus such as Bacillus subtilis, Aspergillus niger, Candida tropicalis, and so on to degrade FG by fermentation of CSM (Sun et al 2013;Yang et al 2012;Zhang et al 2007). Zhang et al (2007) reported that microbial fermentation could greatly decrease FG levels in CSM, but detoxification effects differed among species of microorganisms.…”
Section: Introductionmentioning
confidence: 99%